The relationship between proteinuria and coronary risk: A systematic review and meta-analysis - Perkovic, V.; Verdon, C.; Ninomiya, T.; Barzi, F.; Cass, A.; Patel, A.; Jardine, M.; Gallagher, M.; Turnbull, F.; Chalmers, J.; Craig, J.; Huxley, Rachel (Public Library of Science, 2008)
Background: Markers of kidney dysfunction such as proteinuria or albuminuria have been reported to be associated with coronary heart disease, but the consistency and strength of any such relationship has not been clearly defined. This lack of clarity has led to great uncertainty as to how proteinuria should be treated in the assessment and management of cardiovascular risk. We therefore undertook a systematic review of published cohort studies aiming to provide a reliable estimate of the strength of association between proteinuria and coronary heart disease. Methods and Findings: A meta-analysis of cohort studies was conducted to obtain a summary estimate of the association between measures of proteinuria and coronary risk. MEDLINE and EMBASE were searched for studies reporting an age- or multivariate-adjusted estimate and standard error of the association between proteinuria and coronary heart disease. Studies were excluded if the majority of the study population had known glomerular disease or were the recipients of renal transplants. Two independent researchers extracted the estimates of association between proteinuria (total urinary protein >300 mg/d), microalbuminuria (urinary albumin 30-300 mg/ d), macroalbuminuria (urinary albumin >300 mg/d), and risk of coronary disease from individual studies. These estimates were combined using a random-effects model. Sensitivity analyses were conducted to examine possible sources of heterogeneity in effect size. A total of 26 cohort studies were identified involving 169,949 individuals and 7,117 coronary events (27% fatal). The presence of proteinuria was associated with an approximate 50% increase in coronary risk (risk ratio 1.47, 95% confidence interval [CI] 1.23-1.74) after adjustment for known risk factors. For albuminuria, there was evidence of a dose-response relationship: individuals with microalbuminuria were at 50% greater risk of coronary heart disease (risk ratio 1.47, 95% CI 1.30-1.66) than those without; in those with macroalbuminuria the risk was more than doubled (risk ratio 2.17, 1.87-2.52). Sensitivity analysis indicated no important differences in prespecified subgroups. Conclusion: These data confirm a strong and continuous association between proteinuria and subsequent risk of coronary heart disease, and suggest that proteinuria should be incorporated into the assessment of an individual's cardiovascular risk. © 2008 Perkovic et al.